Expanding digits of a maxillofacial prosthodontist - Sanjna Nayar; U Aruna; Santhosh (Wolters Kluwer Medknow Publications, 2015)
Complete or partial loss of a finger is the most commonly encountered problem in prosthetic dentistry. The etiology of missing digit may either be congenital or acquired. Trauma is the most common cause for acquired defect of the digit. Loss of a digit results in functional and psychological impact on quality-of-life of the patient. This article portrays about the prosthetic management of a patient with an acquired defect of finger